Effect of Different Disinfectants on Bacterial Aerosol Diversity in Poultry Houses - Jiang, Linlin; Li, Meng; Tang, Jinxiu; Zhao, Xiaoyu; Zhang, Jianlong; Zhu, Hongwei; Yu, Xin; Li, Youzhi; Feng, Tao; Zhang, Xingxiao (Frontiers in Microbiology, 2018)
To better understand the effect of different disinfectants on the types and quantities of microorganisms in a broiler chicken house, five different types of disinfectants, including ozone, available chlorine, quaternary ammonium salt, glutaraldehyde and mixed disinfectant , were used. The broiler house microbial communities were analysed by high-throughput sequencing combined with air sampling. The results showed that the concentrations of airborne aerobic bacteria in the empty broiler houses after application of different disinfectants were significantly reduced compared to a house untreated with disinfectant (P<0.05 or P<0.01), and the number of inhalable particles of airborne aerobic bacteria sharply decreased after disinfection. Of the five disinfectants, the mixed disinfectant had the best disinfection efficacy on the total microbial communities (P<0.05). A total amount of 1,094,174 high-quality sequences were obtained by high-throughput sequencing, which identified 1995 operational taxonomic units (OTUs). In sum, 42 phyla and 312 genera were identified. The structures of airborne microbial communities in the broiler houses after the different disinfectants were applied differed. In the house treated with the mixed disinfectant, the microbial communities containing opportunistic pathogens, such as Shigella, Bacillus, and Bordetella, had the lowest abundance, with a significant decrease compared to those untreated with disinfectant in the empty house. The alpha diversity index showed low diversity of the microbial communities in the house treated with mixed disinfectant. In contrast to the other four disinfectants, only a small amount of bacteria were detected in the air sample in the house treated with the mixed disinfactant, more specifically, just four phyla were found; Proteobacteria, Bacteroidetes, Actinobacteria and Firmicutes. The mixed disinfectant produced a positive effect on the disinfection of four phyla, however, it didn't eliminate them. At genus level, in the house treated with the mixed disinfectant, Bacillus, Arenimonas, Shinella could not be detected, while in houses treated with other disinfectants, these bacteria were detected. The high-throughput sequencing results revealed that the combination of multiple disinfectants exhibited a good disinfection efficacy and that this technique could disinfect the air of broiler houses. These results will help guide the development of a reasonable programme for broiler house disinfection.